2003
DOI: 10.1017/cbo9780511481871
|View full text |Cite
|
Sign up to set email alerts
|

The Organ Music of J. S. Bach

Abstract: This is a completely revised 2003 edition of volumes I and II of The Organ Music of J. S. Bach (1980), a bestselling title, which has subsequently become a classic text. This edition takes account of Bach scholarship of the 25 years prior to publication. Peter Williams's piece-by-piece commentary puts the musical sources of the organ works in context, describing the form and content of each work and relating them to other music, German and non-German. He summarises the questions about the history, authenticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…As emerged from our autoethnographic data, the ways in which the various dimensions of identity work helped in coping with, and managing such disruption and threat were highly significant. Given the current lack of research on non-elite, amateur, and older sports participants who engage in sport as serious leisure, and specifically in relation to the role of remedial self-help (Williams, 2003) in injury management, it is hoped that in a small way this article addresses the lacuna.…”
Section: Discussion: Restoration Transformation?mentioning
confidence: 99%
“…As emerged from our autoethnographic data, the ways in which the various dimensions of identity work helped in coping with, and managing such disruption and threat were highly significant. Given the current lack of research on non-elite, amateur, and older sports participants who engage in sport as serious leisure, and specifically in relation to the role of remedial self-help (Williams, 2003) in injury management, it is hoped that in a small way this article addresses the lacuna.…”
Section: Discussion: Restoration Transformation?mentioning
confidence: 99%
“…These events are not exclusive of the Earth but have also been predicted (Dycus 1969;Adolfsson, Gustafson & Murray 1996;Christou & Beurle 1999;Bland & Smith 2000;Christou 2004Christou , 2010Domokos et al 2007;Christou, Vaubaillon & Withers 2008;Christou et al 2012) and observed (Selsis et al 2005;Christou, Vaubaillon & Withers 2007;Hueso et al 2010;Daubar et al 2013) in other planets. The connection between asteroidal debris and bolides was first proposed by Halliday (1987), further explored by Williams (2002Williams ( , 2004 and Jenniskens (2006) and first confirmed observationally by Trigo-Rodríguez et al (2007). Since then, new examples of bolides associated with asteroids have been reported (Trigo-Rodríguez et al 2009Madiedo et al 2013).…”
Section: Introductionmentioning
confidence: 93%
“…The study of musical material in this article is based on: l genre-style analysis, as well as on the theoretical positions of musicologists (Chapin, К., 2010;Mann, A., 1971;1987;McGahie, D. Р., 2006;Pesic, P., 2017;Williams, Р., 2003); l issues of studying polyphony (i.e. many voices) in Chinese musical folklore (Fan Zuyin, 2004;Li Hong, 2015) l specifics of integration processes in Chinese piano art (Bai Ye, 2018), l features of the fret organization of Chinese piano music (Peng Cheng, 2006); l research of professional composer creativity of Chinese creators (Sun Weibo, 2006;Wu Na, 2009); l questions of performance implementations based on the development of the performing principles of polyphony Ying Jiang (2019).…”
Section: Data Collection Tools-documentsmentioning
confidence: 99%